The spread of Covid-19 - London, Martha (Core library guide to Covid-19, 2021)
COVID-19 was first recognized in Wuhan, China, but within a few months it spread to every corner of the globe. The Spread of COVID-19 traces the pandemic during those perilous early months, as health officials and world leaders reacted to the new disease and the scope of its impact became clear.